Sentiment analysis Using Neural Network Models - Islamovich Akhmetgaliev, Aynur; Mubarakovich Gafarov, Fail; Bizyanovna Sitdikova, Farida (International Journal of Psychosocial Rehabilitation, 2024)
The article deals with methods for solving the problem of sentiment analysis based on neural network models of natural language processing. The article considers methods that create a vector representation of words in the n-dimensional vector space, which are based on "Word2Vec," "GloVe," and "FastText" technology. Approaches are used in the tasks of classification, sentiment analysis, typo correction, and recommendation systems. We present the results of classification comparison in the problem of sentiment analysis of a multilayer perceptron, a convolutional and recurrent neural network, decision trees (random forest), support vector machines (SVM), naive Bayes classifiers (NB), and k-nearest neighbors (K-NN). The results of the classification are presented for three data sets: Twitter messages, reviews of various goods and services, Russian-language news